2021
DOI: 10.1038/s41598-021-00947-7
|View full text |Cite
|
Sign up to set email alerts
|

Lactate activates hypothalamic POMC neurons by intercellular signaling

Abstract: Previous studies indicate that the activity of hypothalamic POMC neurons can be regulated by glucose via intracellular mechanisms, but its regulation by lactate is poorly understood. In addition to its energetic role, lactate acts as a signaling molecule. In this study, we evaluated the function and location of the lactate receptor, hydroxycarboxylic acid receptor 1 (HCAR1). We used a conditional genetic approach to label POMC neurons and evaluated their sensitivity to lactate using patch-clamp recordings. l-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 62 publications
(95 reference statements)
1
10
1
Order By: Relevance
“…Importantly, microstructure analyses demonstrated that this effect was due to a decrease in the induction of satiety 14 . Similar results were obtained using electrophysiological recordings, showing that POMC neurons are activated by glucose and this response was lost when MCT1-4 were inhibited in tanycytes 19 or by direct incubation of hypothalamic slices with L-lactate 22 . Here, we demonstrated that the modulation of glucose metabolism in tanycytes is important for the satiety response using behaviour studies.…”
Section: Discussionsupporting
confidence: 82%
“…Importantly, microstructure analyses demonstrated that this effect was due to a decrease in the induction of satiety 14 . Similar results were obtained using electrophysiological recordings, showing that POMC neurons are activated by glucose and this response was lost when MCT1-4 were inhibited in tanycytes 19 or by direct incubation of hypothalamic slices with L-lactate 22 . Here, we demonstrated that the modulation of glucose metabolism in tanycytes is important for the satiety response using behaviour studies.…”
Section: Discussionsupporting
confidence: 82%
“…In agreement with these findings, we confirmed that the levels of hypothalamic leucine were elevated in fasted mice retaining altered metabolic activity, such as hyperphagia and hypoglycemia. Lactate exerts neuronal activity in hypothalamic neurons that controls whole-body energy metabolism, and the shuttling of lactate from tanycytes to POMC neurons is functionally linked to the control of feeding behavior and energy expenditure [ 17 , 18 ]. These previous findings are consistent with our metabolomics results revealing a reduced level of lactate in the hypothalamus of fasted mice.…”
Section: Discussionmentioning
confidence: 99%
“…Such POMC-EGFP mice may be useful in studying hypothalamic neuronal signaling pathways involved in the regulation of glucose homeostasis, leptin activity, feeding behavior, obesity, and depression. Studies using POMC-EGFP mice demonstrated that lactate plays a role of an intercellular messenger in astrocyte-neuron intercellular communication and the regulation of food intake ( Ordenes et al, 2021 ).…”
Section: Spatiotemporal Targeting Of Fluorescent Probesmentioning
confidence: 99%